Non-destructive performance assessment of bonded surface connections by changes in curvature mode shape. (October 2022) - Serratore, Giuseppe; Cosco, Francesco; Mundo, Domenico; Gagliardi, Francesco
Abstract: Joining processes have gained increasing relevance and their effectiveness appears as a necessity in the production of lightweight structures. Many researchers have been investigating affordable testing solutions to assess joint performance. Herein, an easy-to-apply non-destructive technique, based on vibration analysis, is presented and evaluated by a purely numerical approach. Changes in the curvature mode shape of beam-like structures are measured and related to the extension of bonded areas of the connected parts. The preliminary results, achieved by modal analysis, provide a first proof-of-concept of the proposed technique and of its increased sensitivity compared to techniques based on frequency response functions.